Disputable issues of the surgical strabismus correction in patients with Graves’ ophthalmopathy - D.S. Atarshchikov; E.Yu. Korchemkina (РМЖ "Клиническая офтальмология")
D.S. Atarshchikov1, E.Yu. Korchemkina2 1Central Clinical Hospital and Polyclinic of the Department for Presidential Affairs, Moscow, Russian Federation 2Academy of Postgraduate Education of the Federal Scientific and Clinical Center of the Federal Medical Biological Agency of Russian Federation, Moscow, Russian Federation Graves’ ophthalmopathy (GO) is an autoimmune disease characterized by lymphocytic infiltration, fibroblast activation and the accumulation of collagen and glycosaminoglycans in the orbital tissues and extraocular muscles. Ultimately, the inflammatory changes cause restrictive strabismus in 17–51% of patients with GO. Meantime, the percentage of successful surgical management of strabismus in such patients varies within the 11–45% range, and the extent of inflammatory and fibrotic changes differs drastically even between the muscles located within the same orbit. Thus, every surgeon dealing with this problem makes every effort to find an optimal relationship between millimeters of resection or recession and prism diopters based on the published data and individual surgical performance. In the present review based on the analysis of scientific research, the emphasis is made on the most challenging issues of surgical strabismus management an d correction described in medical practice. Patients with GO who visit an ophthalmic surgeon should be cautioned in advance that it could be not possible to achieve fully binocular vision in all directions of gaze. Keywords: Graves’ ophthalmopathy, restrictive strabismus, postoperative drift, extraocular muscles, recession, resection. For citation: Atarshchikov D.S., Korchemkina E.Yu. Disputable issues of the surgical strabismus correction in patients with Graves’ ophthalmopathy. Russian Journal of Clinical Ophthalmology. 2022;22(4):254–257 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-254-257.